Just “Like Coffee” or Neuroenhancement by Stimulants? - Franke, Andreas G.; Koller, Gabriele; Krause, Daniela; Proebstl, Lisa; Kamp, Felicia; Pogarell, Oliver; Jebrini, Tarek; Manz, Kirsi; Chrobok, Agnieszka I.; Soyka, Michael (Frontiers in Public Health, 2021)
Introduction: Pharmacological neuroenhancement (PN) is a topic of increasing importance and prevalence among students. However, there is a lack of differentiating PN substances, according to their psychoactive effects. In particular, there is a lack of data about PN by caffeinated drinks, even if coffee is a common and broadly used Neuroenhancer because of its cognitively enhancing effects regarding wakefulness, alertness and concentration. Materials and Methods: A web-survey was developed for German students and alumni about the non-medical use of caffeine for PN contained questions about coffee, caffeinated drinks and energy drinks, caffeine pills and methylxanthine tea regarding frequency and further contextual factors. Results: Six hundred and eighty-three participants completed the survey. Nearly all participants knew about PN (97.7%). 88.1% admitted using some over-the-counter substances. For PN purposes, coffee was used by 72.9% followed by energy drinks (68.2%) and cola drinks (62.4%). Methylxanthine containing tea was used for PN purposes, too (black tea 52.3%, green tea 51.7%). 1.8% admitted using illegal substances or prescription drugs, too. Discussion: Using legal methylxanthine containing drinks for PN seems to be extremely common with coffee and energy drinks being the preferred substances, while illegal and prescription drugs are only minimally used. Further studies should investigate the awareness of methylxanthine containing drinks as well as its character to be a flavoring drink or a neuroenhancer.